2004
DOI: 10.1021/bi048589s
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Structural Characterization of Transforming Growth Factor Beta Induced Protein (TGFBIp) from Porcine and Human Corneas

Abstract: Mutations in the TGFBI (BIGH3) gene that encodes for transforming growth factor beta induced protein (TGFBIp) are the cause of several phenotypically different corneal dystrophies. While the genetics of these protein misfolding diseases are well documented, relatively little is known about this extracellular matrix protein itself. In this study, we have purified TGFBIp from normal human and porcine corneas using nondenaturing conditions and standard chromatography techniques. The two homologues were shown to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
52
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 35 publications
(59 citation statements)
references
References 48 publications
7
52
0
Order By: Relevance
“…1, B and F, and Table I). In a recent study, we have shown that ϳ60% of human cornea TGFBIp (ϳ65 kDa) is covalently associated with insoluble components of the extracellular matrix and that this insoluble fraction of TGFBIp is released after reduction of disulfides (2). The present results show that the low molecular mass isoforms of TGFBIp (35-45 kDa) in the cornea are not water-soluble indicating that some of these fragments are also associated with insoluble components of the extracellular matrix.…”
Section: Discussionsupporting
confidence: 46%
“…1, B and F, and Table I). In a recent study, we have shown that ϳ60% of human cornea TGFBIp (ϳ65 kDa) is covalently associated with insoluble components of the extracellular matrix and that this insoluble fraction of TGFBIp is released after reduction of disulfides (2). The present results show that the low molecular mass isoforms of TGFBIp (35-45 kDa) in the cornea are not water-soluble indicating that some of these fragments are also associated with insoluble components of the extracellular matrix.…”
Section: Discussionsupporting
confidence: 46%
“…Cloning and Expression of WT and Mutant FAS1-4-The WT and mutant FAS1-4 domains (residues 502-657) were constructed from the corresponding TGFBI clones using the following primers: 5Ј-gcaggtatggggactgtcatggatgtcct-3Ј (forward) and 5Ј-tcatgcttgtttgaagatctcaagcgca-3Ј (reverse), which add two additional amino acids (Ala-Gly) at the N terminus of FAS1-4 domain compared with the native TGFBIp amino acid sequence (SwissProt accession number Q15582) and include the authentic C terminus of corneal TGFBIp (16). PCR products were subsequently cloned into the Champion TM pET SUMO Protein Expression System (Invitrogen) according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…TGFBIp has been found, by sequence identity, to consist of an N-terminal Cys-rich EMI domain (15) and four consecutive fasciclin 1 (FAS1) domains. Furthermore, authentic TGFBIp molecules purified from human and pig corneas exist as monomers with no apparent post-translational modifications (16). TGFBIp has been shown to interact in vitro with numerous macromolecules including several types of integrins (17,18), collagens, and proteoglycans (19,20), indicating that TGFBIp exerts a role in mediating contact between cells and the extracellular matrix.…”
mentioning
confidence: 99%
“…No TGFBIp post translational additions have been reported but when purified from human or porcine corneas, the C-terminal is truncated in a fraction of the purified material (Andersen et al, 2004). This truncation differs in human and porcine corneas and in porcine tissue two isoforms are found.…”
Section: Structurementioning
confidence: 97%